Enhancing Frequency Stability in Multi-Area Grids with High Penetration of Renewable Energy Sources - Dahiru Zailani Lame; Kabiru Sani; D. M. Nazif (Asian Journal of Science, Technology, Engineering, and Art, 2026)
The increasing penetration of intermittent and uncertain renewable energy sources presents substantial challenges to frequency stability in modern power systems. This study aims to enhance frequency regulation in a two-area interconnected power system by comparing conventional and optimization-based control strategies. A detailed Load Frequency Control (LFC) model incorporating governor, turbine, generator, and tie-line dynamics was developed to evaluate system responses to load disturbances. Three control schemes were examined: an Integral controller, a conventional Proportional–Integral–Derivative (PID) controller, and a Particle Swarm Optimization (PSO)-tuned PID controller. PSO was used to optimize the PID parameters by minimizing the Integral of Time-Weighted Absolute Error (ITAE). MATLAB/Simulink simulations showed that the Integral controller produced an overshoot of 0.0164, a settling time of 29.22 seconds, and an ITAE value of 2.2190. The conventional PID controller reduced the overshoot and ITAE value to 0.0026 and 0.5194, respectively, although its settling time increased slightly to 29.98 seconds. The PSO-tuned PID controller achieved the best overall performance, with the lowest overshoot (0.0007), fastest settling time (29.21 seconds), and lowest ITAE value (0.0557). These findings demonstrate that PSO-based PID tuning substantially improves damping and reduces frequency deviations following load disturbances. The study contributes a comparative evaluation of control strategies for multi-area frequency regulation and indicates that PSO-tuned PID control is a promising approach for strengthening the dynamic stability of renewable-integrated power systems, although further practical validation is required before full-scale implementation.